Danantara dan Reformasi Perekonomian Negara dalam Perspektif Teori Keadilan: Antara Pemerataan dan Efisiensi Investasi Negara - Ngabut, Rupertus Arvinci; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2024)
This study aims to analyze the role of Danantara, Indonesia’s sovereign wealth fund, in national economic reform through the lens of distributive justice, particularly based on John Rawls’ theory. Using a normative legal method supported by conceptual and statutory approaches, the research examines Danantara’s legal framework and investment practices through literature and legal documents. The findings reveal that Danantara’s current institutional design lacks sufficient safeguards for transparency, public participation, and equitable benefit distribution, failing to prioritize the least advantaged groups in accordance with Rawls’ difference principle. The novelty of this study lies in its application of justice theory as a critical evaluative framework for public investment policy, diverging from traditional economic or managerial analyses of sovereign wealth funds. By focusing on institutional fairness, this paper contributes a new legal-philosophical dimension to debates on economic governance, emphasizing the need for justice-oriented state investment strategies in developing economies such as Indonesia.